PENGARUH TATA KELOLA (CORPORATE GOVERNANCE) PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL (INTELLECTUAL CAPITAL) - Rio Ariesta Heditya; Dul Muid (Diponegoro Journal of Accounting, 2022)
This study aims to determine the effect of corporate governance on the disclosure of intellectual capital in companies. The sample used consists of some manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020.This study uses multiple regression analysis by conducting analysis on manufacturing companies using purposive sampling method. The number of samples in the study used was 150 companies.The results show that the size of the board of commissioners, the independence of the board of commissioners has a positive and significant effect on the company's intellectual capital research. Furthermore, for blockholder ownership, government ownership and board tenure have a negative and significant effect on intellectual capital.